Intramyocardial fast-SENC is less impacted by compensatory mechanisms while monitoring cardiotoxic effects of chemotherapy than echocardiography and conventional CMR: the PREFECT study. (25th November 2020) - Steen, H; Montenbruck, M; Gersak, B; Schwarz, A.K; Esch, S; Kelle, S; Giusca, S; Korosoglou, G; Wuelfing, P; Dent, S; Lenihan, D
Abstract: Background: Cancer treatments (CT) have been shown to occasionally elicit a toxic reaction on the heart. Echocardiography (ECHO) and cardiac magnetic resonance imaging (CMR) have been used to monitor cardiotoxicity through left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS). Fast-SENC (fSENC) CMR testing directly measures intramyocardial contraction to quantify subtle changes in function capable of detecting cardiotoxicity missed by conventional imaging modalities. The PREFECT study compares fast-SENC vs ECHO in terms of sensitivity of predicting and detecting subclinical (sCTX) or clinical cardiotoxicity (cCTX) irrespective of loading conditions or changes in cardiac output. Methods: A single center, prospective clinical trial of patients receiving anthracycline-based CT had fSENC acquired during CMR exams with a 1.5T scanner. Intramyocardial LV & RV strain was quantified with MyoStrain software. Three short axis scans (basal, midventricular, & apical) were used to calculate peak strain in 16 LV & 6 RV longitudinal segments while three long axis scans (2-, 3-, & 4-chamber) were used to calculate 21 LV & 5 RV circumferential segments. Results: 63 patients had 323 scans; 41% experienced sCTX and 15% cCTX. Figure 1 shows a Box and Whisker's plot for the % of fSENC ≤−17 by cardiotoxicity status. Both fSENC and CMR LVEF detected sCTX and cCTX based on ANOVA analysis (p<0.001) although fSENC had better delineation of both sCTX and cCTX. However, ECHO LVEF and GLS did not detect sCTX or cCTX (p=NS). CMR stroke volume index decreased while blood pressure and heart rate increased for both sCTX and cCTX (p<0.001). Meanwhile, mass index and end-systolic volume index increased for cCTX (p<0.001). Conclusion: Segmental fSENC detected early CT-induced sCTX regardless of loading conditions. ECHO did not detect sCTX potentially due to compensatory mechanisms or acoustic window limitations in breast cancer and lymphoma patients that had less effect on CMR. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Myocardial solution (MSI)